Variation in Density and Shrinkage between Sawmill and Hand Processed Khaya Senegalensis Woodin Sokoto, North-Western Nigeria - A. A, Malami; Y.G, Zubairu; A.K, Nafi’u (International Journal of Sustainable Agricultural Research, 2015)
A research on shrinkage and density variation between sawmill and hand processed Khaya senegalensis timber was conducted to determine the effectiveness of the species in service. The wood samples obtained from Kara market Sokoto were cut into standard sizes for the determination of moisture content, density and shrinkage respectively. Analysis of variance was used to analyze the data. The study reveals that sawmill has an average moisture content of 15.43%, average density of 901.90kg/m3 and volumetric shrinkage of 8.40%. While hand processed Khaya senegalensis has an average moisture content of 15.88%, average density of 812.07kg/m3 and volumetric shrinkage 8.12%. However, density recorded in both sawmill and hand processed Khaya senegalensis wood belongs to high class, suggesting that even the hand processed can serve the low and middle income class satisfactorily and is thus recommended for economic consideration.